Moringa oleifera leaf polysaccharide alleviates experimental colitis by inhibiting inflammation and maintaining intestinal barrier - Mohamed Husien, Hosameldeen; Peng, WeiLong; Su, Hongrui; Zhou, RuiGang; Tao, Ya; Huang, JunJie; Liu, MingJiang; Bo, RuoNan; Li, JinGui (Frontiers in Nutrition, 2022)
The characteristic of ulcerative colitis (UC) is extensive colonic mucosal inflammation. Moringa oleifera (M. oleifera) is a medicine food homology plant, and the polysaccharide from M. oleifera leaves (MOLP) exhibits antioxidant and anti-inflammatory activity. The aim of this study to investigate the potential effect of MOLP on UC in a mouse model as well as the underlying mechanism. Dextran sulfate sodium (DSS) 4% in drinking water was given for 7 days to mice with UC, at the same time, MOLP (25, 50 and 100 mg/kg/day) was intragastric administered once daily during the experiment. Structural analysis revealed that MOLP had an average molecular weight (Mw) of 182.989 kDa and consisted of fucose, arabinose, rhamnose, galactose, glucose, xylose, mannose, galactose uronic acid, glucuronic acid, glucose uronic acid and mannose uronic acid, with a percentage ratio of 1.64, 18.81, 12.04, 25.90, 17.57, 12.01, 3.51, 5.28, 0.55, 1.27, and 1.43%, respectively. In addition, the features of MOLP were identified by Fourier-transform infrared (FT-IR) and spectra, X-ray diffraction (XRD). The results showed that MOLP exhibited protective efficacy against UC by alleviating colonic pathological alterations, decreasing goblet cells, crypt destruction, and infiltration of inflammatory cells caused by DSS. Furthermore, MOLP notably repressed the loss of zonula occludens-1 (ZO-1) and occludin proteins in mucosal layer, as well as up-regulating the mRNA expression of interleukin-10 (IL-10) and peroxisome proliferator-activated receptor-γ (PPAR-γ), whereas down-regulating the activation of Toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), nuclear factor-kappa B (NF-κB) signaling pathway and the production of pro-inflammatory cytokines. Therefore, these results will help understand the protective action procedure of MOLP against UC, thereby providing significance for the development of MOLP.